INNOVATIVE EDUCATIONAL METHODS – A GUARANTEE OF EDUCATIONAL EFFICIENCY - M. J. Saidova (Web of Journals Publishing, 2025)
In order to increase the effectiveness of education, the article discusses the importance of using modern interactive methods in the educational process, and elaborates comprehensive suggestions and recommendations.
Keywords: Modern educational methods, educational efficiency, interactive methods, brainstorming, working in small groups, round discussion, learners, educators, debate, problem situation, educational material